Section for Residents and Fellows‐in‐Training Leaders: Where Are They Now?. (28th April 2014) - Roby, Brianne B.; Wilson, Meghan N.; Raol, Nikhila; Carter, John; Kelley, Kanwar; Deckard, Nathan A.; Yoo, Estelle S.; Dowdall, Jayme R.
Abstract : The purpose of this study was to examine the experiences of prior governing council (GC) members of the American Academy of Otolaryngology—Head and Neck Surgery (AAO‐HNS) Section for Residents and Fellows‐in‐Training (SRF) and assess the impact of early Academy involvement. A survey was conducted via email on all prior AAO‐HNS SRF GC members. The AAO‐HNS SRF has elected 52 GC members since its 2003 inception. Each member served an average of 1.5 year‐long terms. The mean time since completion of training is 4.1 years. A subspecialty fellowship was pursued in 86%. Fifty‐seven percent practice in academic settings, with 3 members advancing to subspecialty division director within their department. More than half (58%) have served on an AAO‐HNS committee, and most are frequent attendees of the annual meeting. All prior members felt involvement in the SRF GC was beneficial, enabling them to gain leadership skills and deeper understanding of the specialty.